STRATEGI PENINGKATAN LAYANAN PUBLIK DESA RIDOMANAH: ADMINISTRASI, KESEHATAN, DAN PENDIDIKAN - Nabawi Asudais, Muhammad Akas; Abidin, Dindin; Ridlo, Azi Faiz (Universitas Islam 45 Bekasi, 2025)
Public service at the village level is directly connected to the community, making service quality a key factor in evaluating government performance. However, Ridomanah Village still faces challenges in administrative services, healthcare access, and education quality. This community engagement program aims to enhance public services in these three sectors through a strategic approach. The method involves digital administration training for village officials, health literacy campaigns, and optimizing educational infrastructure. The program was implemented through training, consultations, technology dissemination, and advocacy. The results show significant improvements, including better administrative efficiency, increased health awareness, and enhanced learning resources for students. Despite some challenges, such as limited infrastructure and digital adaptation, this initiative provides a foundation for sustainable service improvements. Strengthening collaborations with health institutions, expanding digital access, and ensuring continuous evaluation are recommended to maximize the program’s impact on community welfare.